Effect of tin addition on propane dehydrogenation reaction over silica-supported palladium-tin catalysts. - Méndez, Jonathan; Rodríguez, Douglas; Sánchez, Jorge; Arteaga, Geomar (Ciencia)
Ver resumen pdf.